Data science that works : building impactful products for media clients (Data Science Salon, 2019)
"Presented by Lauren Lombardo, Senior Data Scientist at Nielsen. Products underpinned by traditional statistical methods, big data, and artificial intelligence increasingly provide new and unique insight into the rapidly growing media landscape. How can you make sure that your product will have the impact that you expect it to? What factors do you need to consider when developing a product to ensure that the tool is understood by the market and used appropriately? To what extent is this the concern of a data scientist? This talk will discuss how these questions apply to those hoping to deliver data-oriented insight to the media and entertainment industry."--Resource description page